Controlling Domain Wall Oscillations in Bent Cylindrical Magnetic Wires - Altbir-Drullinsky, D (American Physical Society, 2020)
Magnetic cylindrical nanowires are promising candidates for future three-dimensional nanotechnology. Domain walls (DWs) in magnetic nanowires play the role of information carriers, and the development of applications requires proper description of their dynamics. Here we perform a detailed analytical and numerical analysis of the DW motion along a bent magnetic nanowire under the action of tangential magnetic fields. Our results show that the DW velocity, precession, and oscillation frequencies can be controlled by the interplay between the curvature and the external magnetic field. Small magnetic fields induce a DW motion without precession and oscillatory behavior, while higher magnetic fields yield a Walker breakdown regime, in which an oscillatory forward and backward DW motion is observed. Controlled DW motion under the Walker breakdown regime makes magnetic nanowires potential candidates for nanoscale microwave generation and sensing. © 2020 American Physical Society.